The efficacy and safety of androgen analog oxandrolone in improving clinical outcomes in burn patients: a systematic review and meta-analysis of randomized controlled trials - Lou, Jiaqi; Xiang, Ziyi; Zhu, Xiaoyu; Song, Jingyao; Huang, Neng; Li, Jiliang; Jin, Guoying; Fan, Youfen; Cui, Shengyong (Frontiers in Medicine, 2025)
BackgroundThis latest systematic review and meta-analysis aim to examine efficacy and safety of androgen analog oxandrolone in burn patients.MethodsRelevant articles were retrieved from Pubmed, Embase, Cochrane, Web of science, International Clinical Trials Registry Platform, China National Knowledge Infrastructure, VIP Database for Chinese Technical Periodicals, Wanfang database and China Biology Medicine disc. The output measures were the weight loss in catabolic phase, weight gain in recovery phase, lean body mass in recovery phas, operation times, healing time of donor area, length of hospital stay/total body surface area burned (LOS/TBSA%), length of hospital stay (LOS), side effects, infection and mortality. Data were pooled and expressed as relative risk (RR) and standardized mean difference (SMD) with a 95% confidence interval (CI).Results19 studies were included in this systematic review and meta-analysis, with 779 patients who received oxandrolone (treatment group) and 1,227 patients who received standard care or placebo (control group). The pooled data from all included studies demonstrated that the treatment group has significantly reduced weight loss in catabolic phase (SMD = 1.86; 95% CI: −0.13–3.84; p < 0.001, I2 = 95.0%), operation times (SMD = −0.69; 95% CI: −1.84–0.46, p < 0.001, I2 = 96.8%), LOS/TBSA% (SMD = −1.07; 95% CI: −2.43–0.29, p < 0.001, I2 = 98.1%), LOS (SMD = −0.55; 95% CI: −1.32–0.22, p < 0.001, I2 = 97.3%) and increased weight gain (SMD = 0.58; 95% CI: −1.21–2.38, p < 0.001, I2 = 95.1%), as well as lean body mass in recovery phase (SMD = 1.30; 95% CI: −0.47–3.24, p < 0.001, I2 = 95.0%). There were no significant differences in healing time of donor area (SMD = −1.48; 95% CI: −2.18–0.77, p = 0.116, I2 = 53.7%), side effects (RR = 1.13; 95% CI: 0.68–1.87, p = 0.174, I2 = 28.4%) and infection (RR = 0.83; 95% CI: 0.67–1.02, p = 0.639, I2 = 0.0%) between the two groups, and it did not significantly reduce mortality (RR = 1.04, 95% CI: 0.47–2.32, p = 0.013).ConclusionOur meta-analysis showed that oxandrolone supplements are beneficial for burn patients as they significantly reduce the weight loss in catabolic phase, operation times, LOS/TBSA%, LOS, mortality and increase weight gain and lean body mass in recovery phase. However, this intervention has minimal impact on healing time of donor area, side effects and infection.